2018
DOI: 10.1002/chir.23023
|View full text |Cite
|
Sign up to set email alerts
|

Highly enantioselective Michael addition of α‐nitroacetate to α,β‐unsaturated pyrazolamide catalyzed by a bifunctional squaramide

Abstract: A highly enantioselective (91‐ > 99% ee) Michael addition of α‐nitroacetate to α,β‐unsaturated pyrazolamide was developed in the presence of a bifunctional squaramide. Satisfactory isolated yields (42%‐99%) have been achieved with a wide range of α,β‐unsaturated pyrazolamides, albeit acceptor of this type displayed poor reactivity in the precedent reports. The adducts resulting from this protocol are useful synthetic intermediates for further synthetic modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 89 publications
(163 reference statements)
0
5
0
Order By: Relevance
“…The study began with the choice of electrophile: we found it curious that, in the main, acyl pyrazoles disubstituted at the heterocycle (of which 1 a-c are examples) were preferred in literature examples across a range of reactions. [2][3][4][5][6][7][8][9][10] Not being able, a priori, to understand why these would be superior to an unsubstituted analogue, we investigated the addition of 9 to the α,β-unsaturated acylpyrazoles 1 a, 1 c, 21 and 22 in the presence of the bifunctional urea-based catalyst [11] 23 at ambient temperature (Table 1). Preliminary studies demonstrated that dichloromethane was the optimal solvent and 0.1 M a serviceable concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study began with the choice of electrophile: we found it curious that, in the main, acyl pyrazoles disubstituted at the heterocycle (of which 1 a-c are examples) were preferred in literature examples across a range of reactions. [2][3][4][5][6][7][8][9][10] Not being able, a priori, to understand why these would be superior to an unsubstituted analogue, we investigated the addition of 9 to the α,β-unsaturated acylpyrazoles 1 a, 1 c, 21 and 22 in the presence of the bifunctional urea-based catalyst [11] 23 at ambient temperature (Table 1). Preliminary studies demonstrated that dichloromethane was the optimal solvent and 0.1 M a serviceable concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Use of 20 mol % catalyst allowed excellent product yields after 7 days reaction time. Very recently, [10] the same group disclosed that 8 could undergo addition with 1.5 equivalents of ethyl nitroacetate ( 12 ) in the presence of 20 mol % of the bifunctional squaramide catalyst 13 to afford 14 a , b with excellent yield and enantiocontrol but no diastereocontrol. This is potentially problematic, as the ethyl ester is not easily removable using conditions under which the pyrazole, or indeed the aliphatic nitro group, are stable.…”
Section: Introductionmentioning
confidence: 99%
“…[187] *Protodenitration was accompanied by a reduction of a methoxycarbonyl moiety. 2013), [188] Thomson (2013), [189] Zhao (2013), [190] Hayashi (2014), [191] Pascal Jr. (2014), [192] Dixon and Ye (2015), [193] Lu (2015), [194] Gong and Meggers (2015), [195] Enders (2015), [196] Wolf (2016), [197] Dixon (2016), [198] Lu and Xiao (2016), [199] Gu and Tian (2016), [200] You (2017), [201] Hayashi (2017), [202] Ryan and Hyland (2017), [203] Anderson (2018), [204] Liang (2018), [205] Hayashi (2018), [206] Li (2018), [207] Xu and Yuan (2018), [208] Xu and Yuan (2018), [209] Hayashi (2019), [210] Ishikawa (2019) [211] and Ye (2019). [212] *Denitration was accompanied by a reduction of a xanthate ester moiety.…”
Section: The Tyrant Conquers the Field -Tributyltin Hydride-mediated ...mentioning
confidence: 99%
“…In 2018, the same group extended this protocol to α-nitroacetates as the nucleophile. [14] The best results were obtained when the cinchona alkaloids-derived squaramide 2 a was used at 20-30 mol% loading (Scheme 2). The adducts were isolated in satisfactory yields, although as 1:1 diastereoisomeric mixture, due to easy epimerisation of the α-nitroacetate stereogenic centre.…”
Section: Pyrazoleamides As Electrophiles In Organocatalysismentioning
confidence: 99%
“…In 2018, the same group extended this protocol to α‐nitroacetates as the nucleophile [14] . The best results were obtained when the cinchona alkaloids‐derived squaramide 2 a was used at 20–30 mol% loading (Scheme 2).…”
Section: Pyrazoleamides As Electrophiles In Organocatalysismentioning
confidence: 99%